Infants' prelinguistic communicative acts and maternal responses: Relations to linguistic development. Issue 1 (February 2014) - Wu, Zhen; Gros-Louis, Julie
Infant–parent interactions are bidirectional; therefore, it is important to understand how infants' communicative behavior elicits variable responses from caregivers and, in turn, how infants' behavior varies with caregivers' responses; furthermore, how these moment-to-moment interactive behaviors relate to later language development. The current study addressed these concerns by observing 10- to 13-month-old infants' interactions with their mothers and measuring their language outcomes when they were 15 months old. The main results were: (1) infants were more likely to combine vocalizations with pointing when mothers were not looking at the target of the point, and when mothers did not respond about the target of the point; (2) infants' combination of vocalization and pointing behavior, especially those produced when mothers were not attending to the target object of the point, related to infants' comprehension skills at 15 months as measured by the MacArthur Communicative Development Inventory (MCDI); (3) maternal follow-in responses were related to infants' improvement in their comprehension and production scores on the MCDI. These results suggest that infants' own prelinguistic communicative acts that are produced differentially as a function of maternal attention and responses, and the maternal responses that they elicit, contribute to infants' subsequent language development.